MicroPulse Transscleral Laser Therapy Demonstrates Similar Efficacy with a Superior and More Favorable Safety Profile Compared to Continuous-Wave Transscleral Cyclophotocoagulation - Enrico Bernardi; Marc Töteberg-Harms (Journal of Ophthalmology)
Purpose. The aim of this study was to compare effectiveness and safety of MicroPulse transscleral laser therapy (MP-TLT) using the original MicroPulse P3® device and continuous-wave transscleral cyclophotocoagulation (CW-TSCPC) using the G-Probe® device in glaucoma. Methods. Spherical equivalent, intraocular pressure (IOP), best-corrected visual acuity (BCVA), and number of topical or oral ophthalmic pressure-reducing medications were registered at every time point, up to the last follow-up at 12 months. A complete slit-lamp examination was conducted to record the following complications: corneal edema, persistent ocular hypotony (IOP ≤5 mmHg) on two consecutive follow-up visits, choroidal detachment, phthisis bulbi, sympathetic ophthalmia, cystoid macular edema, or other abnormal ocular findings. Success was defined as IOP between 6 and 21 mmHg and >20% reduction in IOP with or without antiglaucoma medications. Results. 47 eyes underwent MP-TLT and 150 CW-TSCPC. At 12 months, success was achieved in 88.6% in the CW-TSCPC group and 87.5% in the MP-TLT group (p = 0.883). In the CW-TSCPC group, eyes achieved a 42.4% IOP reduction (from 28.3 ± 12.3 mmHg to 15.3 ± 6.0 mmHg) and a 31.1% reduction (from 22.0 ± 7.2 mmHg to 15.7 ± 4.8 mmHg) in the MP-TLT group. Visual acuity remained primarily unaltered in both groups. Conclusion. MP-TLT was as effective in lowering IOP as CW-TSCPC and achieved comparable success. Additionally, MP-TLT demonstrated consistent and effective outcomes at every time point. The improved safety profile of MP-TLT allows the therapeutic spectrum to be broadened, granting ophthalmologists’ treatment of glaucoma in earlier stages of glaucoma than those typically treated with CW-TSCPC, i.e., early to moderate and to patients with good central-vision.